Comparing chair time required for systemic agent drug reaction (DR) management to allocated chair time for systemic protocol. Issue 28 (1st October 2022) - Rauw, Jennifer Marie; Anderson, Helen; Parimi, Sunil; Brown, Michelle; Hennessy, Kathleen
Abstract : 40 Background: Chemotherapy scheduling and determining associated nursing resources are complex multiobjective decision problems. Management of DRs are thought to take additional chair and nurse time and should be accounted for in appointment scheduling in order to having an efficiently running clinic. BC Cancer – Victoria is a tertiary care regional site of BC Cancer in Victoria, British Columbia, Canada and currently schedules patients using a regimen-based resource intensity model (Greene et al, 2012). Methods: DRs were tracked in real time over 3 months, where BC Cancer ID, reaction, protocol, agent, cycle number and time of reaction were recorded. Our electronic medical record was interrogated to determine start and end of chair time. We then compared the actual chair time required to manage patients with a DR to scheduled chair time. Results: Thirty reactions occurred, including DRs to paclitaxel (43%), rituximab (13%), docetaxel (10%), nivolumab (7%), oxaliplatin (7%), pertuzumab (7%), bendmustine (3%), and daratumumab (3%). The reactions most commonly occurred with cycles 1 or 2. The averages for total chair time during DR, time from arrival to reaction, and time from reaction to discharge were 281 min (+79.5), 106 min (+ 55), and 171 min (+ 94), respectively. An average of 449 min/month extra were required for DR management above scheduled chair time. Conclusions: The agents precipitating DRs were common and predictable. An average of 7 hours and 29 minutes per month above scheduled chair time was required to manage DRs. This information could be used to more efficiently schedule chair and nursing time. This also highlights the need to minimize the number of DRs as management is resource intensive.Agent Average Cycle number DR occurred at Total Chair Time allocated per protocol (min) Average Actual Total Chair Time (min) Average Actual Reaction to Discharge Chair Time (min) Paclitaxel 1.1 180-300 288 (+93.5) 219 (+79) Rituximab 1.3 90-420 332(+58) 252 (+ 99) Docetaxel 1.25 90-180 273(+49) 169 (+18)